Effects of Clustering in Ad Hoc Networks from Network Utility Maximization Aspect - Mirchev, Miroslav; Trajanov, Dimitar; Filiposka, Sonja (My University, 2008)
In this paper, we study joint end-to-end congestion control and medium access control (MAC) in adhoc networks with fixed wireless channels as a utility maximization problem with constraints that arise from contention for channel access. Scheduling of the transmissions is used, although random access can be used too. We analyze the effects of clustering at both physical and application level on the maximum end-to-end throughput gained in the network. Our results show that the natural clustering tendency of the users works favorably and can improve network performance. Two types of network areas are being considered: square shaped and rectangle shaped. The rectangle shaped topology gave higher maximum end-toend throughput.
Keywords: Ad hoc wireless network, clustering, congestion control, medium access control, network utility maximization